A lexicostatistical evaluation of the chagatai Turkish dictionary - ERKAN KIZILARSLAN (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2021)
The Turkish language, which has been used with various phonetic and semantic changes throughout history, has been classified with different views and nomenclatures. One of these views is the Altaic Language Theory. Gerard Clauson, who wanted to express his opinion in the face of this view, presented his views on the theory by conducting a “lexico-statistical” study of the Turkish language. In this study, which was inspired by Clauson's work, a lexico-statistical evaluation of the Chagatai Turkic dictionaries was made. In the study, based on Clauson's “main articles”, the scope of the Chagatai Turkic dictionaries over a hundred basic words, the origin of the words and the ratio of the quoted words were revealed.